Comparison of Developmental Status of Infants Less Than 24 Months Who Were Born from Mothers in High-Risk Age Groups - Afraz, Fatemeh; Ahmadi Doulabi, Mahbobeh; Sajedi, Firoozeh; Akbarzadeh Baghban, Alireza; Rashidi Fakari, Farzaneh (Advances in Nursing & Midwifery, 2020)
Abstract Introduction: Development in children is a qualitative change in their abilities. When children cannot acquire developmental skills according to age, it shows delayed development. Low and high maternal age during pregnancy is a kind of risk factor for developmental disorders in children. Methods: This is a cross-sectional descriptive comparative study that was performed on 400 women who had less than 19 and over 35 years old during pregnancy and now have 4-24-months infants that referred to health centers Kohgiluyeh and Boyer-Ahmad Province, Iran. Participants were selected through multi-stage random sampling. Data collection instruments were: A demographic, obstetric and the “Ages and Stages Questionnaires” for 4-24 months children. Data analysis was done by using the software SPSS 16, and independent t-test, chi-square and logistic-regression tests were used. Results: The prevalence of developmental delay in infants 4-24-months of mothers fewer than 19 and older than 35 years was 7 percent and 11 percent respectively. In mothers over 35 years old, all domains were higher than the others. In both groups of maternal age, the most delayed development was gross motor; the lowest prevalence of late event in a group of mothers less than 19 years was personal-social skills and in women over 35 years was problem-solving. Conclusions: Pregnancy in ages over 35 and less than 19 years are risk factors for the developmental delay of children and could be prevented by appropriate strategies and training.